2022
DOI: 10.1371/journal.pone.0262854
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of chondroitin sulfate in stem cells derived from umbilical cord blood in rats

Abstract: Chondroitin sulfate (CS) and its isomeric variant, dermatan sulfate (DS), are complex glycosaminoglycans (GAGs) which are ubiquitous components of the extracellular matrix in various tissues including the brain. CS and/or DS are known to bind to a variety of growth factors and regulate many cellular events such as proliferation and differentiation. Although the biological activities of CS and/or DS towards neural stem/progenitor cells (NSPCs) have been well investigated, the CS and/or DS of hematopoietic stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…It was observed that, the majority (88.4%) of the studied women did not attend any health teaching classes related to blood cord stem cell banking and donation. Figure (2): reveals levels of Knowledge regarding blood cord and stem cells among the studied pregnant women. It was observed that more than two third (67.0%) of the studied pregnant women had low level of knowledge regarding blood cord and stem cells and only 11.0% of them had high level of knowledge regarding blood cord and stem cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that, the majority (88.4%) of the studied women did not attend any health teaching classes related to blood cord stem cell banking and donation. Figure (2): reveals levels of Knowledge regarding blood cord and stem cells among the studied pregnant women. It was observed that more than two third (67.0%) of the studied pregnant women had low level of knowledge regarding blood cord and stem cells and only 11.0% of them had high level of knowledge regarding blood cord and stem cells.…”
Section: Resultsmentioning
confidence: 99%
“…The components of cord blood are the same as those found in other blood that can be found in any organ. It is unique, though, because it has an excess of hematopoietic cells (2,3) Hematopoietic stem cells (HSCs) are multi potent primitive cells that can develop into all types of blood cells. HSCs can form mature blood cells, such as red blood cells, platelets, and white blood cells (4).…”
Section: Introductionmentioning
confidence: 99%
“…The sulfation arrangement within HS chains profoundly influences the specificity of interaction [39,40]. Chondroitin sulfate (CS) and its isomeric variant, dermatan sulfate (DS), are major components of the extracellular matrix in various tissues [41]. CS and DS are known to serve as ligands for a variety of growth factors and regulate many cellular events including morphogenesis, proliferation, and differentiation [42].…”
Section: Glycosaminoglycan Modificationsmentioning
confidence: 99%
“…Furthermore, multiple diverse forms of CS/DS (CS A–E) with distinct sulfated disaccharide repeats are present across various species and tissues. Depending on sulfation pattern and IdoA content, CS/DS chains can be classified into different subtypes: CS-A [GlcA-GalNAc(4S)], CS-B/DS [IdoA(2S)-GalNAc(4S)], CS-C [GlcA-GalNAc(6S)], CS-D [GlcA(2S)-GalNAc(6S)], CS-E [GlcA-GalNAc(4S,6S)], and CS-iE [IdoA-GalNAc(4S,6S)] ( 77 , 78 ). Interestingly, these different types of CS exhibit distinct spatiotemporal expression across tissues, particularly in the brain ( 79 , 80 ).…”
Section: Spatial and Temporal Diversity Of Glycosaminoglycansmentioning
confidence: 99%